Strategic renewal of higher education institutions from the perspective of organizational learning: an analytical study in the colleges of Muthanna University - Saleh Abdul Redha Rashid; Ali Abdul Razzaq (Iraqi Journal for Administrative Sciences, 2024)
The study aims to measure the effect of organizational learning practices on achieving strategic renewal. The study presents different opinions about its variables , besides a practical analytical aspect . The study used a questionnaire as atool to gather data from a sample consisting of (65) dean assistants and head departments in the colleges of Al-Muthanna University. The study used the scale of (Celep et al ,2011) to test the four practices of organizational learning (Instructional Practices, Supportive Leadership, Communication and Education, and Cooperation and Information Sharing) ,while the strategic renewal with its two dimensions (Exploitative strategic renewal and Explorative strategic renewal) was measured according to the scale developed by (Al-Ghazali ,2013) . The study reached some conclusions like the clear presence of an orientation in all sampled colleges for practicing knowledge transformation on individuals and group levels to the organizational level and adding institutional frame to it to make it part of its organizational memory. A number of recommendations are presented in the study like the necessity for the colleges to develop their own philosophy regarding organizational learning to make it part of their strategies to achieve the desired strategic renewal.